Effect of intercropping on soil microbial diversity and community network - Li, Lu Xing (Frontiers in Microbiology, 2025)
IntroductionUnderstanding the impact of wheat-soybean intercropping on soil microbial communities is crucial for developing sustainable, agricultural practices.MethodsTo investigated how this intercropping system influences soil microbial diversity and network structures, a field experiment was conducted in 2019 using a randomized block design with three treatments: spring wheat monoculture (W), soybean monoculture (S), and 6:2 wheat-soybean intercropping (SW). The soil physical, chemical, and biological properties were analysed, and DNA was sequenced.Results and discussion:The results showed that the intercropping and sampling location markedly affected bacterial a-diversity, with SW showing a 68.7% higher Shannon index and a 15.0% higher Simpson index than W. Although there were no significant differences in eukaryotic α-diversity and β-diversity between SW and W treatments, unique species distributions were observed. Co-occurrence network analysis revealed that intercropping enhanced the complexity and stability of both the bacterial and eukaryotic communities. Distance-based redundancy analysis (dbRDA) indicated that the soil properties, particularly total phosphorus, available phosphorus, pH, and easily oxidizable carbon, were significantly correlated with the bacterial community composition. While easily oxidizable carbon was the main factor influencing soil eukaryotic community. In conclusion, SW positively regulates soil microbial communities, enhancing bacterial diversity and fostering more stable microbial networks. This study provides a theoretical basis for adopting intercropping to promote agricultural sustainability. Nonetheless, long-term research is needed to explore community shift functions and their long-term impacts on soil health and productivity for sustainable farming.